The Role of Neuron Growth Factor and Interleukin-10 in The Development of Pain in Adenomyosis: A Narrative Review - Agus Heriyanto; Dian Tjahyadi; Anita Rachmawati; Luky Adlino (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: Adenomyosis, a benign uterine condition characterized by endometrial tissue within the myometrium, leads to uterine enlargement, infertility, dysmenorrhea, and heavy menstrual bleeding. While its precise etiology remains elusive, delayed pregnancy may contribute to its increasing incidence among infertile women. This condition, predominantly affecting parous women, is also associated with higher rates of early miscarriage. Although immune dysregulation in endometriosis is well-documented, comparable research in adenomyosis is limited.Objective: This review aims to explore the roles of Interleukin-10 (IL-10), an anti-inflammatory cytokine, and Neuronal Growth Factor (NGF), a neuroimmune factor, in adenomyosis.Discussion: Elevated IL-10 levels in ectopic endometrial tissue suggest a potential immunosuppressive mechanism that may exacerbate symptoms. NGF is also implicated in the pain and inflammation associated with adenomyosis. A deeper understanding of the interplay between IL-10 and NGF could offer critical insights into the inflammatory nature and pain mechanisms of this condition.Conclusion: This review proposes IL-10 as a potential inflammatory biomarker and NGF as a pain marker in adenomyosis, paving the way for future research into novel therapeutic targets. Elucidating these pathways could lead to treatments focused on mitigating inflammation and alleviating associated symptoms of adenomyosis.Keywords: adenomyosis; neuronal growth factor; interleukin-10; pelvic pain Peran Neuron Growth Factor (NGF) dan Interleukin-10 (IL-10) dalam pembentukan Nyeri pada Adenomyosis : Sebuah Review NaratifAbstrakPendahuluan: Adenomyosis, suatu kondisi rahim jinak yang ditandai dengan adanya jaringan endometrium di dalam miometrium, menyebabkan pembesaran rahim, infertilitas, dismenore, dan perdarahan menstruasi yang berat. Meskipun etiologi pastinya masih belum jelas, kehamilan yang tertunda kemungkinan berkontribusi pada peningkatan insidennya di kalangan wanita infertil. Kondisi ini, yang sebagian besar memengaruhi wanita multipara, juga dikaitkan dengan tingkat keguguran dini yang lebih tinggi. Meskipun disregulasi imun pada endometriosis telah didokumentasikan dengan baik, penelitian serupa pada adenomyosis masih terbatas.Tujuan: Tinjauan ini bertujuan untuk mengeksplorasi peran Interleukin-10 (IL-10), sitokin anti-inflamasi, Faktor Pertumbuhan Saraf (NGF) dan faktor neuroimun dalam adenomyosis.Diskusi: Peningkatan kadar IL-10 dalam jaringan endometrium ektopik menunjukkan mekanisme imunosupresif potensial yang dapat memperburuk gejala. NGF juga berperan dalam nyeri dan peradangan yang terkait dengan adenomyosis. Pemahaman yang lebih dalam tentang interaksi antara IL-10 dan NGF dapat memberikan wawasan penting mengenai sifat inflamasi dan mekanisme nyeri dari kondisi ini.Kesimpulan: Tinjauan ini mengusulkan IL-10 sebagai biomarker inflamasi potensial dan NGF sebagai penanda nyeri pada adenomyosis. Hal tersebut membuka jalan bagi penelitian lebih lanjut untuk target terapeutik baru. Menguraikan jalur-jalur ini dapat mengarah pada perawatan yang berfokus pada mitigasi peradangan dan mengurangi gejala adenomyosis.Kata kunci: adenomiosis; interleukin-10; neuronal growth factor; nyeri pelvis.